A Review on The Efficacy of Seashell’s Waste as Alternative Abrasive Agent in Toothpaste - Mohd Zulfanis, Marissa; Sanusi, Shahmir Hayyan (Research Progress in Mechanical and Manufacturing Engineering, 2022)
While the ingredients may differ slightly, toothpastes from all brands overall contain the same general ingredients which are mild abrasive, binders, humectants, flavouring agents, sweeteners, colouring agents, preservatives, active ingredients and others. The abrasive specifically are made up of different types depending on the company’s designation and one of it being the calcium carbonate. Calcium carbonate can be found in chalk, limestone, marbles and seashells. Seashells is a type of mollusc that contains very high calcium carbonate content ranging from 95% to 98%. In seashells harvesting districts, it is found that abundance of seashell waste are being heaped by the beach and causing pollutions such as soil pollution and odour pollution. This thesis study the significant and effectiveness of using seashell waste as alternative abrasive agent for toothpaste. Different type of mollusc were used to represent the seashells and they are mussels, clam, oyster and cockle. From the results obtained, all of them shows very similar results and the final test which is the validation test, clearly proves that using seashells as abrasive agent are efficient in removing stains on the teeth as the depth scratch made by all the different seashells are deeper than the thickness of the artificial stain which represents the actual teeth stains.